2020
DOI: 10.1186/s12886-020-01696-3
|View full text |Cite
|
Sign up to set email alerts
|

Ocular coloboma combined with cleft lip and palate: a case report

Abstract: Background Ocular coloboma is an excavation of ocular structures that occurs due to abnormal fusion of the embryonic optic fissure. Further, cleft lip/palate (CL/P), a congenital midline abnormality, is caused by a defect in the fusion of the frontonasal, maxillary, and mandibular prominences. No study has reported the association between these two phenotypes in the absence of other systemic abnormalities. We present a case of ocular coloboma along with CL/P and without other neurological abnormalities. Case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…These changes were observed in patients with CL/CLP without systemic or neurological involvement, excluding syndromic associations. The chief complaint of these patients was low visual acuity reported or observed in an ophthalmic examination, reinforcing the importance of ophthalmic follow-up, early diagnosis, and immediate intervention for a good visual prognosis [4,6].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These changes were observed in patients with CL/CLP without systemic or neurological involvement, excluding syndromic associations. The chief complaint of these patients was low visual acuity reported or observed in an ophthalmic examination, reinforcing the importance of ophthalmic follow-up, early diagnosis, and immediate intervention for a good visual prognosis [4,6].…”
Section: Discussionmentioning
confidence: 78%
“…In the study by Anchlia et al [3] Previously published case reports describe ocular abnormalities in patients with orofacial clefts, resulting from the abnormal fusion of the embryonic optic fissures, such as ocular coloboma, ectopia lentis, ectopia pupillae, and bilateral optic disc pit with maculopathy [4,6]. These changes were observed in patients with CL/CLP without systemic or neurological involvement, excluding syndromic associations.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Vitamin A deficiency, maternal diabetes, maternal hypothyroidism, and numerous pharmaceutical agents have been associated with sporadic coloboma formation. 2 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…6 Previous studies have found mutations in various genes associated with microphthalmia, anophthalmia, and coloboma (MAC) phenotypes. 7 Typical iris and retinochoroidal coloboma is a relatively common finding which results from the failure of choroidal fissure closure when the embryogenesis is complete in the first three months of gestational life. 8 However, in our case, except for iris coloboma with high intraocular pressure, no other abnormalities were found in the posterior segment of the eye.…”
Section: Discussionmentioning
confidence: 99%